Budaya Populer dalam Praktek Keagamaan - Saragih, Rim Glory Phasah; Turnip, Sonny H. (Marturia, 2021)
Abstract Culture is an important part of the life of a church, especially in Indonesia. Everything related to culture will remain relevant in everyday life and when talking about culture it must be applied that culture is not only silent and will continue to move according to the times. However, on the other hand, certain church cultures are still adhered to by historical heritage or ethnicity, where this condition forms a high barrier and wall between religion and popular culture. In this paper the author will discuss religious practices in the Indonesian context and how popular culture in Christianity is also Islam. This paper will also look at how popular culture has had an impact on religious practice in Indonesia, as well as how popular culture has actually become a medium for developments in religious practice, whether in worship or in religions that adhere to that religion. Abstrak Budaya menjadi bagian penting dalam hidup bergereja terkhusus di Indonesia. Segala hal yang terkait dengan budaya akan tetap relevan dalam kehidupan sehari-hari dan kalau berbicara budaya popular maka harus dipahami bahwa budaya itu tidak hanya diam dan akan terus bergerak sesuai dengan perkembangan jaman. Namun di sisi lain budaya gereja tertentu masih terpaut kepada warisan sejarah atau juga suku di mana kondisi ini yang terkesan memberi sekat dan dinding yang tinggi antara agama dan budaya populer. Dalam tulisan ini penulis akan membahas praktek ke-agamaan dalam konteks Indonesia dan bagaimana budaya populer terlibat di dalamnya baik agama Kristen juga agama Islam. Tulisan ini juga akan melihat bagaimana dampak yang diberikan oleh budaya populer terhadap praktek keagamaan di Indonesia, juga bagaimana budaya populer tersebut justru menjadi media bagi perkembangan dalam praktek keagamaan, baik itu dalam ibadah atau juga di dalam pengajaran kepada umat yang menganut agama tersebut.